Prevalence and antibiotic-resistance of Salmonella isolated from food in Morocco - Brahim Bouchrif; Bianca Paglietti; Manuela Murgia; Andrea Piana; Nozha Cohen; Moulay Mustapha Ennaji; Salvatore Rubino; Mohammed Timinouni (Journal of Infection in Developing Countries)
Background: Salmonellosis remains one of the most frequent food-borne diseases worldwide, especially in developing countries. The emergence of antimicrobial resistance in Salmonella isolates from food can potentially compromise the treatment of these infections. This investigation was conducted for the first time in Morocco both to detect the occurrence of Salmonella in foods as well as to determine the antibiotic resistance profile of the Salmonella isolates. Methodology: In total, 11,516 food samples collected from 2002 to 2005 were investigated. Isolated Salmonella were characterized by serotyping and susceptibilities were determined for 15 antimicrobial drugs using the disc diffusion assay. Results: The overall percentage of Salmonella prevalence (n=105) was 0.91% with rates of 71% for slaughterhouses and 9% for seafood. Sixteen different serotypes were identified among 104 Salmonella enterica isolates including serotypes Infantis (n=25), Bredeney (n=13), Blokley (n=11), Typhimurium (n=9), Mbandaka (n=8), Branderup II (n=7), and Kiambu (n=6); 1 isolate of Salmonella enterica belonged to subspecies II salamae. Twenty-nine percent of isolates (n=30/105) were resistant to at least one antimicrobial. Resistance to tetracycline was the most common finding (21%), followed by resistance to ampicillin (13%), amoxicillin+clavulanic acid (9%), streptomycin (7%), chloramphenicol (4%) and nalidixic acid (3,8%). None of the isolates was resistant to 3rd-cephalosporin and fluoroquinolones (i.e. ciprofloxacin). Multidrug resistance (MDR) was seen in 9.5% of the isolates, mainly in S.. Typhimurium DT104 with R-type ACSSuT and S. Hadar. Conclusions: Despite a low frequency of Salmonella isolation, S. Typhimurium DT104 was identified in the first step of the food chain. The study points out the need control antibiotic resistance in Salmonella isolated from food in Morocco to avoid the spread of MDR.